O uso do jornal nas aulas de português: leitura, interpretação textual e gramática normativa - (:unkn) unknown (Universidade Federal do Pampa, 2021)
This article aims to verify how teachers understand the use of newspapers in the classroom as a means of teaching and learning textual genres, with a focus on reading and grammar, combined with the practice of teaching in Portuguese and the form of interpretation of facts. It seeks to reflect on the concepts and uses of different journalistic genres and their relevance for teaching and learning reading and writing; verify the importance of different journalistic texts for the teaching of grammar; lead the student to learn to read and evaluate different points of view, differentiating positions, opinions and facts, and collaborate for the development of students' critical sense and argumentation. Exploring journalistic texts makes it possible to expand the universe of students, it helps in the formation of competent readers and makes classes more interesting, in addition to presenting great value for the introduction of certain linguistic concepts. The methodology used brought relevant contributions from several authors, including: Augusto (2004); Azevedo (2019); Diana (2020); Faria (2008); Hamze (2020); Santos, Souza and Teixeira (2019), among others that are also important to carry out this work. The results show that the use of newspapers in the classroom, both printed and digital, contributes as a source of information that can generate knowledge for critical analysis and relevant discussions for the formation of critical and autonomous readers, helping, deepening and expanding the process of teaching and learning writing.
Keywords: Formação docente; Literatura; Gênero textual jornalístico; Teacher Training; Literature; Journalistic Textual Genre; CNPQ::LINGUISTICA, LETRAS E ARTES